2010
DOI: 10.1007/s00127-010-0239-6
|View full text |Cite
|
Sign up to set email alerts
|

Suicide in high security hospital patients

Abstract: The suicide rate among high security hospital patients was significantly higher than in the general population. Women were especially at risk while resident, whereas for men, the risk was higher after discharge.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
2
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 39 publications
1
27
2
1
Order By: Relevance
“…However, such data are not readily available and it is often challenging and very costly to collect such data (Jones and Swerdlow, 1998). Thus, we opted for the use of the general population as the standard as is commonly done in epidemiological and demographic studies, including in industrialized countries (Breslow and Day, 1987a;Jones and Swerdlow, 1998;Ackers et al , 2011;Crook et al, 2003;Datiko and Lindtjorn, 2010;Jones et al, 2011;Kamper-Jorgensen et al, 2008;Reulen et al, 2010;Secrest et al, 2010;Symmons et al, 1998;Trombert-Paviot et al, 2008;Wilson et al, 2010;Brinkhof et al, 2009). …”
Section: Choice Of the Standard Populationmentioning
confidence: 99%
“…However, such data are not readily available and it is often challenging and very costly to collect such data (Jones and Swerdlow, 1998). Thus, we opted for the use of the general population as the standard as is commonly done in epidemiological and demographic studies, including in industrialized countries (Breslow and Day, 1987a;Jones and Swerdlow, 1998;Ackers et al , 2011;Crook et al, 2003;Datiko and Lindtjorn, 2010;Jones et al, 2011;Kamper-Jorgensen et al, 2008;Reulen et al, 2010;Secrest et al, 2010;Symmons et al, 1998;Trombert-Paviot et al, 2008;Wilson et al, 2010;Brinkhof et al, 2009). …”
Section: Choice Of the Standard Populationmentioning
confidence: 99%
“…Forensic psychiatric patients present challenges to treatment providers due to their complex problem constellations, with major mental disorders in combination with criminal behaviour and psychosocial problems (1-5). The pronounced vulnerability of this patient group can be seen in increased mortality and suicide risk when compared to the general population (2,6,7).…”
Section: Introductionmentioning
confidence: 99%
“…A survey of suicides in UK high secure hospitals spanning 29 years (1972 to 2000) found increased rates of suicide among in-patients compared with the general population (Jones 2011). More interestingly, it found that women in high security were more than twice as likely to complete suicide than men, which is a significant deviation from the trend seen in general population.…”
Section: Clinical Depression Psychological Distress and Self-harmmentioning
confidence: 59%